Comparison Shopping Agents and Online Price Dispersion: A Search Cost based Explanation - Pathak,Bhavik K (Universidad de Talca, 2012)
Search costs and consumer heterogeneity are two important explanations for the price dispersion in the brick and mortar (B&M) markets. Comparison shopping agents (CSAs) provide a single click decision support for consumers’ purchasing related decision problems and reduce their search costs by providing detail price dispersion related information. Contemporary researchers in IS observe that even with such negligible search costs, price dispersion still continues in the online markets. Consumer heterogeneity and retailer heterogeneity have been agreed upon as two primary explanations for online price dispersions. In this paper, popular CSAs are analyzed to check if they provide complete and accurate price dispersion information. It is shown that because of the selection bias and temporal delay in updating information, contemporary CSAs may not present complete and accurate price dispersion information. In order to reach to an optimal purchasing decision, consumers may have to rely on a sequential search across multiple CSAs or browse through various retailers. This research adds a search cost dimension to explain the continuance of price dispersion in the online markets.